Gender diversity within companies: Challenges and opportunities in skills management - BOUMEGOURA, Naim (Journal of Human Sciences, 2025)
Gender diversity within businesses presents both challenges and opportunities in skills management. While ensuring equitable representation, diverse teams offer varied perspectives, fostering innovation and problem-solving. Managing skills amidst this diversity involves recognizing biases, implementing inclusive policies, and providing equal growth opportunities. Effective skills management enhances productivity, engagement, and organizational performance. By embracing diversity, companies cultivate a more inclusive work culture and gain a competitive edge.